Liquidity-adjusted CAPM: An empirical analysis on Indian stock market - Gaurav Kumar; Arun Kumar Misra (Cogent Economics & Finance, 2019)
This article examines the impact of various sources of systematic liquidity risk and idiosyncratic liquidity risk on expected returns in the Indian stock market. The study tested the liquidity-adjusted capital asset pricing model (LCAPM) which is previously tested on developed markets. Systematic liquidity risk is found to be significant in impacting asset returns through various channels, viz. commonality in liquidity and illiquidity sensitivity to market returns. Covariance between individual stock returns and associated stock liquidity has a commanding influence as an idiosyncratic liquidity risk factor. The estimated asset pricing model is found to be robust across the two sub-time periods. The findings indicate that given the multidimensional nature of risk, the alternative of LCAPM along with the idiosyncratic risk is persuasive for consideration in investment decisions.
Keywords: G10; G12; G15; 330; illiquidity; liquidity risk; NSE; emerging market; liquidity-adjusted CAPM